Elementary Processes in Organic Photovoltaics - Leo, Karl.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume presents the results of a multi-year research programme funded by the Deutsche Forschungsgemeinschaft (German Research Council), which explains how organic solar cells work. In this new promising photovoltaic technology, carbon-based materials are deposited by low-cost methods onto flexible substrates, thus allowing devices which open completely new applications like transparent coatings for building, solar cells integrated into clothing or packages, and many more. The investigation of organic solar cells is an interdisciplinary topic, covering physics, chemistry and engineering. The different chapters address topics ranging from the synthesis of new organic materials, to the characterization of the elementary processes such as exciton transport and separation, and the principles of highly efficient device design.
From the contents: Polymeric solar cells: Molecular orientation, structure, and optoelectronic performance -- An integrated approach towards highly efficient bulk-heterojunction solar cells based on dendritic oligothiophenes -- Organic solar cells based on oligothiophene derivatives -- Charge separation at nanostructured molecular donoracceptor interfaces -- p-B-n organic junctions for efficient photovoltaics -- Interplay between microscopic structure and intermolecular charge transfer processes in polymer-fullerene bulk-heterojunctions -- Organic solar cells from optimized self-assembling block copolymers with controlled nanoscale morphology.
Keywords: Polymers; Optical materials; Renewable energy sources; Semiconductors; Physical chemistry; Electronics; Polymers; Optical Materials; Renewable Energy; Semiconductors; Physical Chemistry; Electronics and Microelectronics, Instrumentation